The physiological load imposed on basketball players during competition - McInnes, S. E.; Carlson, J. S.; Jones, C. J.; McKenna, M. J. (Journal of Sports Sciences, 1995)
In this study, the intensities of activity and movement patterns during men's basketball were investigated by videoing the movements and monitoring the heart rate and blood lactate responses of eight elite players during competition. The results are expressed according to 'live time', which is actual playing time, and 'total time', which includes live time as well as all stoppages in play. The mean (+/- S.D.) frequency of all activities was 997 +/- 183, with a change in movement category every 2.0 s. A mean total of 105 +/- 52 high-intensity runs (mean duration 1.7 s) was recorded for each game, resulting in one high-intensity run every 21 s during live time. Sixty percent of live time was spent engaged in low-intensity activity, while 15% was spent in high-intensity activity. The mean heart rate (HR) during live time was 169 +/- 9 beats min-1 (89 +/- 2% peak HR attained during laboratory testing); 75% of live time was spent with a HR response of greater than 85% peak HR. The mean blood lactate concentration was 6.8 +/- 2.8 mM, indicating the involvement of glycolysis in the energy demands of basketball. It is concluded that the physiological requirements of men's basketball are high, placing considerable demands on the cardiovascular and metabolic capacities of players.